SUBUH DALAM AL-QUR’AN: ANALISIS MAKNA SUBUH DALAM KITAB TAFSIR AS-SA’DI KARYA ABDURRAHMAN AS-SA’DI - Fakih, Muhammad; Mursalim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Subh time is the beginning phase of the day that holds an important position in Islamic teachings. The Qur’an describes this time through several terms such as as-subh, al-fajr, bukrah, and as-sahr, each of which carries its own linguistic meaning and distinct spiritual implications. This study aims to examine the meaning of subh in the Qur’an based on the interpretation of Abdurrahman As-Sa’di in Tafsir As-Sa’di. This research employs a library study method with a thematic (maudhu’i) approach, namely by collecting all verses related to subh time and analyzing their interpretations in As-Sa’di’s work. The results of the study show that the three main terms, as-subh, al-fajr, and bukrah, directly refer to the time of subh, while as-sahr describes the final part of the night before dawn. As-Sa’di’s interpretation emphasizes the dimensions of tranquility, blessing, and the beginning of acts of worship associated with the subh time. Subh is portrayed as a time filled with the first light, witnessed by angels, and serves as a moment for spiritual preparation for human beings. This study demonstrates that subh time carries profound meanings that are not only linguistic in nature, but also encompass important moral and spiritual dimensions in the life of a Muslim.